Beyond Binary Opposition Thinking in Environmentalism: Using Chris Okezie Ijiomah’s Harmonious Monism to Integrate Anthropocentric and Ecocentric Worldviews - Besong, Eric (Studia Ecologiae et Bioethicae, 2026)
This paper argues that the perceived divide between anthropocentric and ecocentric perspectives on human-nature relations can be bridged by Chris Okezie Ijiomah’s philosophical framework of Harmonious Monism. Anthropocentrism, which prioritises human interests, and ecocentrism, which assigns intrinsic value to nature, have long been treated as opposing worldviews. Moving beyond this dichotomy, Harmonious Monism offers an integrative framework that recognises the complementarity of humans and nature. Through its principles of balance, tolerance and interconnectedness, I propose a reconciling perspective in which ecological value and human needs are seen not as mutually exclusive, but as interdependent. This harmonising worldview thus has the potential to transcend the anthropocentric/ecocentric divide and promote a more holistic and ethically grounded human-nature relationship. Rather than treating human and ecological interests as opposites, I employ harmonious monism to present them as interdependent realities within the environment. The emphasis on balance, tolerance and interconnectedness reflects that all beings - human and non-human - coexist and contribute to a greater whole. This avoids privileging one side over the other; instead, it calls for ethical practices that support both human flourishing and ecological integrity as mutually reinforcing goals.